Factors Associated with Mothers’ Care of Their Newborns in Saudi Arabia - Ibrahim M. Gosadi (Ubiquity Press, 2019)
Background: Infant mortality rates are highest in the southern regions of Saudi Arabia, compared to other regions in the kingdom. Objective: To measure demographic factors associated with mothers’ levels of knowledge and practice of care for their newborns in Jazan region, south of Saudi Arabia. Methods: This is a cross-sectional study conducted between November and December 2018 in Jazan region, Saudi Arabia, on the northern borders of Yemen. A questionnaire was utilised to measure mothers’ level of knowledge and practice of newborn care. Data was collected via interviews, and a scoring system was developed to classify knowledge level and practice adequacy. Logistic regression was used to assess the presence of statistically significant associations between demographic factors and level of knowledge and practice adequacy. Findings: A total of 450 mothers participated in the current investigation. A majority of participating mothers were able to give correct answers, where the mean level of knowledge was 11.85/16 [SD: 2.6]. Additionally, the mean score for practice adequacy was 7.11/10 [SD: 1.45]. However, 122 mothers (27%) reported using alternative treatments to treat their newborns instead of seeking professional health care from available health services. Additionally, 42 mothers (9.3%) reported not attending any antenatal visits during their pregnancy. Factors which were found to be statistically associated with knowledge were education level, employment status, and adherence to antenatal visits during pregnancy (p < 0.05). Age and employment status appeared to be associated with practice where older and employed mothers had higher odds of competency (p < 0.05). Conclusions: The proportions of correct answers measuring knowledge and practice adequacy concerning newborn care varied between 40% to 93%. Knowledge and practice appeared to be associated with demographic factors, such as level of education, age, and attending antenatal care visits.